1956
DOI: 10.1177/003591575604901211
|View full text |Cite
|
Sign up to set email alerts
|

Discussion on the Functional Activities of the Basophil Cells of the Pituitary Gland

Abstract: TBE object of this paper is to summarize the present state of knowledge concerning the conditions which give rise to hyalinization of basophil cells and to the formation of basophil cell adenomata in the rat pituitary. The hyalinization and basophil adenomata which are found in the human pituitary in cases of the Cushing syndrome will be discussed in the light of the implications of the observations which have been made in the rat.Three types of basophil cell in the rat.-In the pars distalis of the rat pituita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1958
1958
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…28 She expanded the understanding of the physiological function of corticotrophic activity in pituitary "intermediate" zones, areas of basophilic cell invasion in Cushing disease, and the hyalinization seen in these cells upon pathological change. 29,30 Finally, she provided excellent clinicopathological descriptions of less common cerebral neoplasms, including rare meningeal tumors, ectopic pinealomas, cerebral medullo-epitheliomas, and gangliogliomas. [31][32][33][34]…”
Section: After Mcgill-a Neuropathological Legacymentioning
confidence: 99%
“…28 She expanded the understanding of the physiological function of corticotrophic activity in pituitary "intermediate" zones, areas of basophilic cell invasion in Cushing disease, and the hyalinization seen in these cells upon pathological change. 29,30 Finally, she provided excellent clinicopathological descriptions of less common cerebral neoplasms, including rare meningeal tumors, ectopic pinealomas, cerebral medullo-epitheliomas, and gangliogliomas. [31][32][33][34]…”
Section: After Mcgill-a Neuropathological Legacymentioning
confidence: 99%
“…Excess numbers of basophil cells appear in the pituitary upon the administration of cortisone (32). Purves (33) and Crooke (34) hold that this results not from diminished ACTH secretion but from increased production of follicle-stimulating hormone, and indeed Kovacs et al (31) have found such an increase. Nonetheless, pituitary basophilism appears only in the presence of an excess qf the corticosteroids.…”
Section: Anterior Pituitarymentioning
confidence: 98%